Noninvasive ventilation usage time and survival rate in patients with acute respiratory failure: some key insights. Issue 2 (20th July 2020) - Hukins, Craig; Murphy, Michelle; Edwards, Timothy
We would like to thank Y.M. Madney and colleagues for their considered comments. The data in our recent study are predominantly related to the hypercapnic group reflecting the demand for noninvasive ventilation (NIV) [1]. We agree that the hypercapnic and hypoxaemic respiratory failure (HRF) cohorts were not matched, which is not unexpected when considering that the pathogensis of these two entities are very different. We have previously demonstrated that there are poorer outcomes with hypoxaemic than hypercapnic respiratory failure in a respiratory high dependency unit [2], and there is an increasing proportion of patients with HRF managed in high dependency units. We believe that our recent study indicates that the two entities have different dose–response relationships for NIV but agree that a larger HRF cohort is required to determine the dose characteristics of this group. Dose–response characteristics of noinvasive ventilation differ between hypoxaemic and hypercapnic respiratory failure https://bit.ly/2SYitiC